Does community engaged Carnegie status matter for county health rankings in the United States?. (18th June 2019) - Apatu, Emma; Stallings-Smith, Sericea; Alvarez, Elizabeth; Anderson, Laura; Spaulding, Aaron
Abstract: Background: Community engagement is commonly used to address social inequities. The Carnegie Foundation offers an optional designation for which U.S. colleges and universities may apply to facilitate better educational outcomes through the institutionalization of community engagement. This study is the first to examine the relationship between Carnegie community engaged status and community health outcomes. Methods: Ordinal logistic regression was conducted to investigate the association between the presence of a community engaged institution and county health outcomes, including health behaviors, clinical care relating to access and quality, social and economic factors, and physical environment from the 2016 Robert Wood Johnson County Health Rankings and 2015 New England Resource Center for Higher Education Community engaged list. We examined 820 U.S. counties containing a university or college, 240 of which had a community engaged designation. Results: Findings indicated that the presence of a community-engaged institution was positively associated with Clinical Care (OR = 1.99; 95% CI: 1.09, 3.64). Other county health factors were not similarly associated. Conclusions: Our findings suggest that community engagement status may be most relevant for achieving better access and quality of clinical care. More research is needed to explore this association in the U.S. and internationally.